2018
DOI: 10.1038/s41592-018-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

The GAGOme: a cell-based library of displayed glycosaminoglycans

Abstract: Glycosaminoglycans (GAGs) are essential polysaccharides in normal physiology and disease. However, understanding of the contribution of specific GAG structures to specific biological functions is limited, largely because of the great structural heterogeneity among GAGs themselves, as well as technical limitations in the structural characterization and chemical synthesis of GAGs. Here we describe a cell-based method to produce and display distinct GAGs with a broad repertoire of modifications, a library we refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
146
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 57 publications
9
146
0
2
Order By: Relevance
“…Here we demonstrated that CS56 staining is moderately associated with CHSY1 expression in human glioma tissue (r s = 0.676), suggesting that other CS modification enzymes, such as DSE and CHSTs, may also modulate CS56 epitopes. As a previous report suggested that the CS56 monoclonal antibody preferentially binds to 6-O-sulfated CS 33 and a recent gene knock-in experiments revealed that CHST3-mediated 6-O-sulfation exclusively induced strong CS56 binding 34 , accordingly, our CS56 staining data partially reflect the quantity of CS and suggests that CHSY1 may mediate the increases of 6-O-sulfated CS in human glioma.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Here we demonstrated that CS56 staining is moderately associated with CHSY1 expression in human glioma tissue (r s = 0.676), suggesting that other CS modification enzymes, such as DSE and CHSTs, may also modulate CS56 epitopes. As a previous report suggested that the CS56 monoclonal antibody preferentially binds to 6-O-sulfated CS 33 and a recent gene knock-in experiments revealed that CHST3-mediated 6-O-sulfation exclusively induced strong CS56 binding 34 , accordingly, our CS56 staining data partially reflect the quantity of CS and suggests that CHSY1 may mediate the increases of 6-O-sulfated CS in human glioma.…”
Section: Discussionsupporting
confidence: 70%
“…the GAGOme library developed with CRISPR/Cas9 knockout and knock-in technology, the key enzymes participating in VAR2SCA binding have been identified 34 . The knockout experiments revealed that CHSY1 is an essential CS elongation enzyme required for VAR2SCA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports also show successful expression of active sulfotransferase enzymes in E. coli . It is important to note here that sulfotransferase expression in E. coli might not be as straightforward as in eukaryotic culture systems due to the complexities associated with their post‐translational modification and folding. Here, we engineered E. coli to accumulate PAPS, the least explored of the three critical components described above.…”
Section: Introductionmentioning
confidence: 92%
“…β3GalT1, β3GalT2, β3GalT3/β3GalNAcT1, β3GalT4 and β3GalT5) are involved in the biosynthesis of glycoproteins and glycolipids [11], compensation for galactosyltransferase II deficiency in zebrafish by other b3galt family members is unlikely. Chinese hamster ovary B3galt6 KO cells were also shown to be capable of producing GAGs, in contrast to Xylt2, B4galt7 or B3gat3 KO cells [37]. The recent identification of the presence of a non-canonical trisaccharide linkage region, lacking one Gal residue (GlcA-Gal-Xyl-O-), as a minor constituent in the PG bikunin in the urine of healthy human individuals [28], prompted us to examine the composition of the GAG linkage region in our b3galt6 KO zebrafish models, by analyzing protein extracts from adult b3galt6 -/and WT zebrafish via LC-MS/MS.…”
Section: Discussionmentioning
confidence: 94%